2021
DOI: 10.1016/j.ejso.2020.04.056
|View full text |Cite
|
Sign up to set email alerts
|

Trends and outcome of neoadjuvant treatment for rectal cancer: A retrospective analysis and critical assessment of a 10-year prospective national registry on behalf of the Spanish Rectal Cancer Project

Abstract: Introduction: Preoperative treatment and adequate surgery increase local control in rectal cancer. However, modalities and indications for neoadjuvant treatment may be controversial. Aim of this study was to assess the trends of preoperative treatment and outcomes in patients with rectal cancer included in the Rectal Cancer Registry of the Spanish Associations of Surgeons. Method: This is a STROBE-compliant retrospective analysis of a prospective database. All patients operated on with curative intention inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 27 publications
(20 reference statements)
1
6
0
Order By: Relevance
“…Moreover, our results demonstrated a good concordance (82%) between multimodal imaging findings and pathological results against 63-69% reported in the literature [22,27,40]. As a consequence, we observed a lower number of overstaged patients (9.8%), in contrast to average reported rates ranging from 15% to 24% [25,[45][46][47][48][49][50]. Moreover, the percentage of understaged patients was 8.2% in our study population, while it ranged from 12 to 24% in previous studies [22,25,40].…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, our results demonstrated a good concordance (82%) between multimodal imaging findings and pathological results against 63-69% reported in the literature [22,27,40]. As a consequence, we observed a lower number of overstaged patients (9.8%), in contrast to average reported rates ranging from 15% to 24% [25,[45][46][47][48][49][50]. Moreover, the percentage of understaged patients was 8.2% in our study population, while it ranged from 12 to 24% in previous studies [22,25,40].…”
Section: Discussionsupporting
confidence: 84%
“…There are several studied that have investigated the predictive value of 18 F -FDG PET-CT in the LARC and in recurrent rectal cancer, and more are likely to be produced using collaborative, international research platforms [18][19][20][21][22][23][24][25][26][27]. However, these studies have some limits mainly due to the methodological heterogeneity secondary to their multicentric nature in terms of preoperative studies, chemoradiotherapy, patients' characteristics and PET study method (timing, technique and analysis of images).…”
Section: Discussionmentioning
confidence: 99%
“…Neoadjuvant long-course chemoradiation is associated with improved local control and reduced toxicity compared with postoperative chemoradiation. 13 14 National Comprehensive Cancer Network guidelines recommended preoperative concurrent chemoradiotherapy as a standard of care for stage 2/3 locally advanced rectal cancer. 15 Clinical trials (FFCD 92-03 and EORTC 22921) showed significant improvement in the complete pathological response and local control rate staging with preoperative concurrent chemoradiotherapy compared with preoperative radiotherapy alone.…”
Section: Introductionmentioning
confidence: 99%